Evolving Concepts of Functional Localization. - McCaffrey, Joseph B. (Philosophy Compass, 2023)
Functional localization is a central aim of cognitive neuroscience. But the nature and extent of functional localization in the human brain have been subjects of fierce theoretical debate since the 19th Century. In this essay, I first examine how concepts of functional localization have changed over time. I then analyze contemporary challenges to functional localization drawing from research on neural reuse, neural degeneracy, and the context‐dependence of neural functions. I explore the consequences of these challenges for topics in philosophy of science and philosophy of mind including localizationist versus anti‐localizationist approaches to cognitive neuroscience, multiple realizability, reverse inference in functional neuroimaging, and the modularity of mind.